Chemical composition and size distribution of summertime PM2.5 at a high altitude remote location in the northeast of the Qinghai–Xizang (Tibet) Plateau: insights into aerosol sources and processing in free troposphere - J. Z. Xu; Q. Zhang; Z. B. Wang; G. M. Yu; X. L. Ge; X. Qin (Atmospheric Chemistry and Physics, 2015)
Aerosol filter samples were collected at a high-elevation mountain observatory (4180 m a.s.l.) in the northeastern part of the Qinghai–Xizang (Tibet) Plateau (QXP) during summer 2012 using a low-volume sampler and a micro-orifice uniform deposit impactor (MOUDI). These samples were analyzed for water-soluble inorganic ions (WSIs), organic carbon (OC), elemental carbon (EC), water-soluble organic carbon (WSOC), and total organic nitrogen (TON) to elucidate the size-resolved chemical composition of free tropospheric aerosols in the QXP region. The average mass concentration of the sum of the analyzed species in PM2.5 (particle matter) (WSIs + OC + EC + TON) was 3.74 μg sm−3, 36% of which was sulfate, 18% OC, 17 % nitrate, 10% ammonium, 6.6% calcium, 6.4% TON, 2.6% EC, 1.5 % sodium, 0.9% chloride, 0.5% magnesium, and 0.3% potassium. The size distributions of sulfate and ammonium peaked in the accumulation mode (0.32–0.56 μm), whereas the size distributions of both nitrate and calcium peaked in the range of 1.8–3.2 μm, suggesting the formation of nitrate on mineral dust. OC, EC and TON were also predominantly found in the accumulation mode. The bulk chemical composition and the average oxidation degree of water-soluble organic matter (WSOM) were assessed using a high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS). WSOM was found to be highly oxidized in all PM2.5 samples with an average oxygen-to-carbon atomic ratio (O / C) of 1.16 and an organic mass-to-organic carbon ratio (OM / OC) of 2.75. The highly oxidized WSOM was likely related to active cloud processing during upslope air mass transport coupled with strongly oxidizing environments caused by snow/ice photochemistry. High average ratios of OC / EC (7.6) and WSOC / OC (0.79) suggested that organic aerosols were primarily made of secondary species. Secondary organic aerosol (SOA) was estimated on average accounting for 80% (62–96%) of the PM2.5, indicating that SOA is an important component of free tropospheric aerosols over the northern QXP.